Self-healing performance of concrete blended with novel high-strength capsules - Chuanyi Ma; Liyu Chen; Honglei Chang; Bojie Meng; Ning Zhang; Zhaofeng Li (Case Studies in Construction Materials)
The incorporation of self-healing capsules in concrete often compromises its mechanical properties, limiting their wide-scale engineering application. To address this challenge, this study first develop novel high-strength capsules which can effectively enhance the self-healing ability of concrete without diminishing its mechanical properties. The effects of these capsules are evaluated by using pre-fabrication crack observation, water permeability test, compressive strength test, and ultrasonic test. In addition, SEM-EDS is applied to examine the microstructure and chemical composition of healing products. The experimental results indicate that the impact of the high-strength capsules on both compressive and flexural strength is minimal. Within a specific crack width range, the crack healing rate increases rapidly and then slows down along with the increase of capsule dosage and particle size. As the initial crack width grows, the crack healing rate of specimens decreases across all capsule dosages and particle sizes with varied degrees. However, the decreasing rate of specimens blended with capsules is significantly reduced compared to specimens without capsules. Over the time, the water impermeability gradually increases, showing rapid initial gains that taper off. After 28 days, specimens with a capsule dosage of 3 % exhibit more than a double the water impermeability compared to those without capsules. Furthermore, capsules significantly improve the compressive strength recovery rate of the matrix. SEM-EDS results show that the healing products of the capsules primarily consist of C-S-H, CaCO3, ettringite, and Mg (OH)2, among which C-S-H and CaCO3 are being the most prevalent, correlating with the capsule healing agent’s composition.